Ecofriendly hydrogen production from abundant hydrogen sulfide using solar light-driven hierarchical nanostructured ZnIn2S4 photocatalyst - Chaudhari, Nilima S.; Bhirud, Ashwini P.; Sonawane, Ravindra S.; Nikam, Latesh K.; Warule, Sambhaji S.; Rane, Vilas H.; Kale, Bharat B. (Green Chemistry, 2011)
It is quite well-known that refineries are producing huge amount of H2S which has been used to produce sulphur and water using the well-known Claus process. This process is not an economically viable process, due to the high-cost chemical process and creates further acute environmental problems. Therefore, we have demonstrated the conversion of poisonous H2S into H-2 using an ecofriendly phocatalysis process which is a green unconventional energy source. We have investigated ecofriendly nanostructured ZnIn2S4 photocatalyst to produce hydrogen from H2S using solar light. We also demonstrate the controlled synthesis of hierarchical nanostructured ZnIn2S4 using a facile hydrothermal method. The morphologies obtained have been greatly influenced by the presence of triethylamine (TEA) with various concentrations during the reaction. Surprisingly, a highly crystalline hexagonal layer structured ZnIn2S4 was obtained instead of cubic spinel. The hierarchical nanostructure, i.e. marigold flower-like morphology, was obtained without any surfactant. The thin and transparent petals self-assembled to form the unique nanostructured marigold flower. The highly crystalline puffy marigold flowers and nanoplates/nanostrips were obtained using TEA-assisted hydrothermal synthesis. Optical study shows the band gap in the range of 2.34-2.48 eV. Considering the band gap in the visible region, ZnIn2S4 is used as photocatalyst for hydrogen production from hydrogen sulphide under solar light which is hitherto unattempted. The constant photocatalytic activity of hydrogen evolution, i.e. 5287 mu mol h(-1), was obtained using such hierarchical nanostructured ZnIn2S4 under visible light irradiation. It is noteworthy that the H-2 evolution rate obtained is much higher compared to earlier reported photocatalysts. Considering the significance of morphologies for photocatalytic application, the formation mechanism has also been furnished. The unique hierarchical nanostructured ZnIn2S4 ternary semiconductor having hexagonal layer will have potential applications in solar cells, LEDs, charge storage, electrochemical recording, thermoelectricity and other prospective electronic and optical devices.

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C